High‐yield recombinant expression of the chicken antimicrobial peptide fowlicidin‐2 in Escherichia coli. (2nd February 2015) - Feng, Xingjun; Xu, Wenshan; Qu, Pei; Li, Xiaochong; Xing, Liwei; Liu, Di; Jiao, Jian; Wang, Jue; Li, Zhongqiu; Liu, Chunlong
<x xml:space="preserve">Abstract</x> The antimicrobial peptide fowlicidin‐2 identified in chicken is a member of the cathelicidins family. The mature fowlicidin‐2 possesses high antibacterial efficacy and lipopolysaccharide (LPS) neutralizing activity, and also represents an excellent candidate as an antimicrobial agent. In the present study, the recombinant fowlicidin‐2 was successfully produced by Escherichia coli (E. coli) recombinant expression system. The gene encoding fowlicidin‐2 with the codon preference of E. coli was designed through codon optimization and synthesized in vitro. The gene was then ligated into the plasmid pET‐32a(+), which features fusion protein thioredoxin at the N‐terminal. The recombinant plasmid was transformed into E. coli BL21(DE3) and cultured in Luria‐Bertani (LB) medium. After isopropyl‐β‐D‐thiogalactopyranoside (IPTG) induction, the fowlicidin‐2 fusion protein was successfully expressed as inclusion bodies. The inclusion bodies were dissolved and successfully released the peptide in 70% formic acid solution containing cyanogen bromide (CNBr) in a single step. After purification by reverse‐phase high‐performance liquid chromatography (RP‐HPLC), ∼6.0 mg of fowlicidin‐2 with purity more than 97% was obtained from 1 litre of bacteria culture. The recombinant peptide exhibited high antibacterial activity against the Gram‐positive and Gram‐negative bacteria, and even drug‐resistant strains. This system could be used to rapidly and efficiently produce milligram quantities of a battery of recombinant antimicrobial peptides as well as for large‐scale production. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:369–374, 2015